The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1074/jbc.m005433200
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory Receptor Trafficking Involves Conserved Regulatory Steps

Abstract: Olfactory receptors are difficult to functionally express in heterologous cells. They are typically retained in the endoplasmic reticulum of cells commonly used for functional expression studies and are only released to the plasma membrane in mature cells of the olfactory receptor neuron lineage. A recently developed olfactory cell line, odora, traffics olfactory receptors to the plasma membrane when differentiated. We found that undifferentiated odora cells do not traffic olfactory receptors to their surface,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
59
0

Year Published

2005
2005
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 37 publications
1
59
0
Order By: Relevance
“…2E). The punctuated distribution of OR17-40 in the plasma membrane is similar to what has been reported for other ORs (8,14) and suggests receptor clustering. At Ϸ30 min after ACP labeling, the punctuated pattern on the cell surface gave rise to cytosolic bright spots (Fig.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…2E). The punctuated distribution of OR17-40 in the plasma membrane is similar to what has been reported for other ORs (8,14) and suggests receptor clustering. At Ϸ30 min after ACP labeling, the punctuated pattern on the cell surface gave rise to cytosolic bright spots (Fig.…”
supporting
confidence: 67%
“…In highly expressing cells, ORs did not exit the ER, possibly because of receptor self-aggregation. Previous studies on OR expression in the odora olfactory sensory neuron cell line proposed a model in which receptor trafficking is controlled at two regulatory checkpoints: first, at the exit from the ER, which is crucial in heterologous cells; and second, in a post-Golgi compartment where ORs are blocked in undifferentiated odora cells (8). Our results indicate that, in heterologous cells, the first checkpoint is critical but OR17-40 does not remain blocked at the second, because the receptor was visible at the cell surface only a few hours after being in the Golgi apparatus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have also demonstrated that postGolgi transport of GPCRs is a regulated process. For example, G protein-coupled olfactory and chemokine receptors are released from the ER, but accumulated in the Golgi (16,17). The opsin mutant E150K is also accumulated in the cis and medial Golgi (18).…”
mentioning
confidence: 99%
“…Receptors involved in defensive signaling may be built as ion channels, G protein-coupled receptors (GPCRs), or accessory coreceptors that work in combination with another receptor. A few coreceptors that facilitate cell surface expression (10)(11)(12) and, in some cases, affect the pharmacology of associated receptors (13,14) have been identified. For example, receptor activity-modifying proteins (RAMPs) affect the pharmacology of their GPCR partners (15).…”
mentioning
confidence: 99%